2020
DOI: 10.47197/retos.v0i39.79347
|View full text |Cite
|
Sign up to set email alerts
|

Genética y fútbol: asociación de los polimorfismos genéticos ACTN3 y ACE-I/D en jugadores de fútbol: Revisión literaria (Genetic and soccer: association of ACTN3 and ACE-I/D genetic polymorphisms in soccer players: Literary review)

Abstract: Se ha comprobado y establecido que alrededor del 66% de los componentes del rendimiento y estado del atleta se explican por los factores hereditarios. Dos de los polimorfismos genéticos mas estudiados con relación al rendimiento deportivo en la ultima década, son el ACTN3 R577X y el ACE I/D. El objetivo de este estudio fue resumir las posibles asociaciones de ambos polimorfismos y el rendimiento en jugadores de fútbol, determinando la combinación alélica y genotípica que más destaca en esta población y,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(41 reference statements)
0
0
0
1
Order By: Relevance
“…Additional data revealed that even though muscle injuries represent a severe problem in soccer, it is observed that the preventive models and risk factors existing in the literature are not yet sufficient to promote a significant reduction in the number of muscle injuries in soccer (Clos et al, 2019;Ekstrand et al, 2023). Therefore, there is evidence base supporting the integration of genetic information to help reduce muscle injury in soccer through individualized training programs based on a player's genetic predispositions (Lim et al, 2021;Maestro et al, 2022;Moya, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data revealed that even though muscle injuries represent a severe problem in soccer, it is observed that the preventive models and risk factors existing in the literature are not yet sufficient to promote a significant reduction in the number of muscle injuries in soccer (Clos et al, 2019;Ekstrand et al, 2023). Therefore, there is evidence base supporting the integration of genetic information to help reduce muscle injury in soccer through individualized training programs based on a player's genetic predispositions (Lim et al, 2021;Maestro et al, 2022;Moya, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle injury in soccer represents a complex process influenced by multifactorial parameters (Mandorino et al, 2023;Uchamocha et al, 2024). Recently, genetic factors have been attributed to a role in the susceptibility to muscle injury, the efficiency of recovery mechanisms, and the potential implications for athletic performance (McAuley et al, 2022;Moya, 2021). Genetic polymorphisms have been associated with non-contact muscle injuries in soccer (Lim et al, 2021, Maestro et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…It´s suggested that genetics, muscle fiber type and glycolytic capacity should be considered as factors that influence sprint performance. (Moya et al, 2021;Metaxas et al, 2019;Ratel e Duché e Williams, 2006). It´s importante to highlight that sprint performance is associated to maximum strength, (Peñailillo et al, 2016;Silva;Nassis;Rebelo, 2015), power (Randell et al, 2010) and running technique (Haugen;Mcghie;Ettema, 2019), thus, it´s interesting to reflect on the influence of RT, technical, and coordenative sprint exercises on training transfer and consequently performance.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios han demostrado respecto al polimorfismo de ECA, un predominio del alelo D en deportistas que practican deportes de fuerza y velocidad (Ben Zaken et al, 2015;Garton et al, 2018;Santoro et al, 2019). Por otro lado, respecto al polimorfismo del ACTN3, algunas investigaciones han reportado el predominio del genotipo RR o RX en deportistas de elite y su relevancia en el rendimiento de fuerza y velocidad (Andrade-Mayorga et al, 2019;Arroyo, 2020;Astorino et al, 2018;João et al, 2015). Respectos a aspecto genéticos, a la fecha, se desconocen investigaciones que hayan estudiado estas variables en tenimesistas chilenos, que debido a las características de juego podrían ser relevantes.…”
Section: Introductionunclassified